Economic allocation of reliability growth testing using Weibull distributions. (August 2016) - Awad, Mahmoud
Abstract: Reliability growth testing (RGT) has been widely used for assessing the reliability of complex systems in many industries such as automotive, aerospace, and oil and gas industry. The traditional common and practiced approach of RGT is to assess the initial reliability of the system by building and testing few prototypes for a period of time that extends from few months to years. Then, based on the initial reliability, initial testing time, and reliability target; the total testing time is determined using power law based models such as Duane and AMSAA/Crow models. In this paper, a new method is proposed to allocate RGT time for both subsystems and system level in order to minimize system failure intensity under limited cost and time resources. Unlike existing methods, failure intensity is assumed to be dynamic and modeled using Weibull distribution. Modeling using Weibull is more realistic and increases the applicability of the proposed method in real life applications. The proposed method is motivated by real life examples and its effectiveness is demonstrated by real-life examples. Highlights: RGT time allocation for both subsystems and system level. Minimize system failure intensity under limited cost and time resources. Failure intensity is assumed to be dynamic and modeled using Weibull distribution.